Modern approaches to registration and simplified system of taxation of natural persons-entrepreneurs. - Chernyavska, Yu.B; Zinchenko , M.M. (Ways to Improve Construction Efficiency, 2023)
Modern challenges in the conditions of war and pandemic require a quick response in the economic sphere, since it is the foundation that holds the military front. And therefore, stopping the economy will "bleed" the already extremely depleted budget. The task of the state is to prevent enterprises from stopping, as well as to stimulate small business, which has always been a powerful source of filling the state treasury. The purpose of the study is to simplify the registration, management and taxation of small businesses, including construction, as much as possible. The article analyzes the new changes in the Tax Code of Ukraine (Tax Code of Ukraine) taking into account the simplified system of taxation of individual entrepreneurs. The main advantages of legal business conduct are identified, various options for its registration (including remote) are shown, new possible options for generating an electronic signature are presented, the issue of business legalization without registration of a sole proprietorship and those who can take advantage of such an opportunity is considered, and what changes are subject to sole proprietorship payers 1-3 groups of the unified tax in 2023, the peculiarities of their document flow and taxation during the period of martial law, given specific advice on filling out declarations by entrepreneurs; a number of errors for which FPOs deprive the payer of the single tax, as well as typical errors of self-registration of FPOs, are defined; an alternative approach to the preferential taxation system for the construction business has been revealed, which will make it possible to take advantage of the simplified taxation system. Several points have been highlighted to improve the requirements for taxpayers of the 1-3 groups of the single tax by the state (in particular, adequate consideration of the inflation factor), a number of encouraging steps have been revealed from power structures to starting your own business. The issue of digitization and development of modern electronic services for taxpayers was also on the agenda. Today, digitization is considered a necessary factor for the functioning of public enterprises. This procedure should become simple, understandable, convenient, easy and familiar in application for any average citizen of Ukraine. And such a transformation is possible thanks to the implementation of the e-cabinet in the taxpayer's profile.